Management of State Islamic Religious College Towards a World Class University - Tuala, Riyuzen Praja; Wachidah, Nor Rochmatul (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
This study aims to identify and analyze the managerial efforts undertaken by  State Islamic University of Raden Intan Lampung in its pursuit of becoming a world-class university. A qualitative approach with a case study method was employed. Data were collected through interviews, observations, and documentation. The data analysis process involved data reduction, data presentation, and conclusion drawing. The validity of the data was tested using both source triangulation and technique triangulation. The findings reveal several managerial dimensions implemented by State Islamic University of Raden Intan Lampung in its efforts toward achieving world-class university status. In the planning phase, the university has developed a master plan, strategic plan, and operational plan. During the organizing phase, an international office was established. In the implementation phase, the university has focused on improving the quality of learning inputs, processes, and outcomes; enhancing research and community service; upgrading human resource quality; and strengthening infrastructure and financial management. In the monitoring phase, the Quality Assurance Unit and its staff are optimized to conduct monitoring and evaluation through self-assessments, quality audits, and the preparation of accreditation rankings, in accordance with the Higher Education Institution Accreditation standards. These standards cover education, research, community service, human resources, student affairs, governance, and infrastructure. This research contributes to the development of a distinctive management strategy that integrates Islamic values with international standards, supporting State Islamic Higher Education Institution  in their journey to become World Class Universities.